Meta Analysis of Pesantren's Economic Research - Solihah Sari Rahayu; Aam Slamet Rusydiana; Mochamad AE Dunuraeni (UIN Sunan Gunung Djati Bandung, 2020)
This study tries to review the research around Islamic boarding school (Pesantren) economy on reputable journal. It uses descriptive statistical analysis based on selected 79 article publications or paper related to Islamic boarding school economy, with national and international journal. The entire sample journal publications have published for twelve years from 2007 to 2019. The Results show that Islamic boarding school economy research study case is still dominated by East Java (29%), following by West Java (20%) and Central Java (6%). In addition, the average time of journal publication is between 11 and 12 years. There are at least 20 journals that publish Islamic boarding school economy articles and the most research with Shirkah: Journal of Economics and Business, Economica: Jurnal Ekonomi Islam, Advances in Social Science. Furthermore, the comparison of qualitative research (77%) is still more than the quantitative approach (13%) and mix method approach (10%).